Advanced strategies for designing the structure of lithium-selective membranes and its performance: a mini-review - Troitskiy, Vasiliy; Ponomar, Maria; Ruleva, Valentina; Butylskaia, Tatiana; Gorobchenko, Andrey; Dammak, Lasaad; Mareev, Semyon; Sharafan, Mikhail; Butylskii, Dmitrii (Frontiers in Membrane Science and Technology, 2026)
In recent years, the development of lithium-selective membranes (LSMs), among which the most widely used are ion-imprinted membranes (IIMs), lithium-ion sieve membranes (LISMs) and supported liquid membranes (SLMs), has attracted great interest due to the possibility of their use in direct lithium extraction (DLE) processes. This approach can be an alternative to the DLE sorption processes that are currently closest to commercialization. Although the efficiency of new LSMs has been widely discussed in original works and recent reviews, they are difficult to compare due to the different parameters used to estimate it. Fundamental principles of ion transport underlie the path to improved membrane performance. Success in membrane structure design on the way to its optimization are expressed by the «trade-off» effect: high selectivity of lithium extraction leads to low productivity. This mini-review presents the results of the analysis of recent studies in the field of design and testing of different types of lithium selective membranes. The performance and selectivity of the developed materials were evaluated using identical parameters: specific flux and selective ion separation coefficient. This facilitates an understanding of the path to improving LSMs and scaling it up for application in lithium extraction from brines and eluates of spent lithium-ion batteries.